Analysis of Business Strategy of Clinic X in Denpasar City - Veranita, Mira; Magaline, Monica Beatrice; Pratama, Muhamad Rizal Hadi; Wulandari, Ni Nyoman Feby; Haryadi, Pande Made Doddy (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Clinic X in Denpasar City, Bali Province is the first level health facility in Bali that provides primary health services and a training center for health workers, requiring effective and efficient strategic tactics for the advancement and development of clinics so they can compete in this increasingly modern era. This research was conducted with the aim of conducting an analysis of the strategic plan for Clinic X in the city of Denpasar, Bali Province in dealing with competition in health services. The research method used is descriptive qualitative on primary data and secondary data. Research results are processed by SWOT analysis. The results showed that Clinic X had greater strengths than Weaknesses when viewed from the internal side. From the external side, Clinic X has a greater threat than opportunity. After analysis, X strong clinic has the opportunity to continue to progress and develop. Therefore it can be concluded that Clinic X can focus more on expanding cooperation with BPJS by increasing promotions to compete in the BPJS market and maintaining service quality by proposing monitoring and evaluation activities to be carried out regularly in accordance with indicators determined using a market penetration strategy. This strategy is translated into a more concrete strategy to be monitored and evaluated in assessing the achievement of the strategy.